Sanaston aktiivisen kartuttamisen metodiikkaa. Mallina inarinsaameen luodut biologian uudissanat - Olthuis, Marja-Liisa (Kotikielen Seura, 2003)
A methodology for active enlargement of vocabulary in Inari Sami (englanti)4/2003 (107)A methodology for active enlargement of vocabulary in Inari SamiInari Sami, one of the three Sami languages in Finnish Lapland, has been transformed in just a few years from a dying language spoken principally at home into an official language of the Sami community and a school and university teaching language. With this dramatic change in the social status of the language, a lot of artificially created new words have had to be formulated. The article describes the process of creating a biology vocabulary for Inari Sami and focuses on the word formation methodology followed in forming neologisms for the language.The vocabulary of a neighbouring language is often used as the model when creating neologisms, and for Inari Sami this model has been the vocabulary of Finnish and, to some extent, Northern Sami. These languages have a similar morphological structure, and so neologisms in Inari Sami have usually followed the same structure: compound words from the model have become compound words in Inari Sami, derivatives have mostly become derivatives, and basic words (neither compounds nor derivatives) have generally become basic words. The structure of the model word does therefore appear to be an important factor guiding word formation.The use and acceptance of neologisms in Inari Sami is based on the familiarity principle: the most readily accepted words are those that are familiar from the Finnish language. The most convenient way of forming compound words is by loan translations from Finnish. If a direct translation is not possible, the gap in the vocabulary must be filled by inventing a neologism for the missing element, or by borrowing a word or using a descriptive translation. In derivation, a neologism can be transferred from one language to another piece by piece from the model word (i.e. root and suffix separately), or a neologism created that is reminiscent of its model as far as possible. Basic words should ideally be ...